IMPLEMENTANSI AUGMENTED REALITY DALAM PEMILIHAN MENU MAKANAN DI FOOD COURT BERBASIS ANDROID - Erick, Erick; Ekawati, Nia (LPPM Universitas Putera Batam, 2021)
Technological developments are currently growing, one of which is augmented reality which is popular with the community, many companies have started using augmented reality to offer goods and food. Therefore, Foodcourt A2 needs to use augmented reality in order to attract customer attention in food selection through the application. The method used is the waterfall method which consists of requirements, design, implementation, testing and maintenance. The result of this study is an android-based food menu selection information system that makes it easier for customers to choose food menus.